REFLECTION OF THE SOCIAL STANDARDS AS A CONDITION OF A SUCCESSFUL SOCIALIZATION OF THE CHILDREN WITH A HIGH CREATIVE POTENTIAL - Antonina L. Leutina (Образование и наука)
The aim of this article is to study the problem of reflection of social norms and its impact on the process of socialization of children with a high creative potential.Methods. Processes of socialization and reflection of social norms are considered in this article on the basis of the methodology of the system and mental activity analysis developed by G. P. Schedrovitsky, the founder of the Moscow Methodological Study Group. The article provides the comparative analysis of the adaptation and activity approach to socialization of children with a high creative potential according to such parameters as the object, socialization mechanisms, characteristics of social norms, social controls, personal controls, personal qualities, level of social mobility, and nature of the process of socialization.Results and scientific novelty. The author puts forward the thesis about irrational character and «off-limits» of judgements of the majority of social norms in a modern society, and shows distinction of social and personal regulators of a reflection of these norms. One of the main conclusions is the following: rationalisation and reflection of social norms are the important conditions of social dynamics and social development.It has been found that unconscious personal acceptance of social norms that is typical of the adaptation approach leads to two opposite results: 1) successful adaptation due to uncritical acceptance of social norms by the child, which leads to decrease in the diversity of ways of activity and specificity of its products, and, as a result, failure to realize the creative potential; 2) desocialization of the child in case of keeping the level of creative abilities and the possibility of its realization.The activity approach which is based on reflexive mechanisms represents absolutely different methodological opportunities for solving the problem of socialization of children with a high creative potential. The activity approach contributes to the instrumental attitude of the individual to the process of social interaction, process of autonomy and preserving the personal identity of the human being due to the possibility of establishing this interaction and reconstructing the social norm in a group.Practical significance. The approaches to socialization provided in the article can help practicing teachers to organize their work more effectively, efficiently and qualitatively.